Peningkatan Layanan Keuangan Sekolah Berbasis E-Payment - Sri Wahyuni; Ibnu Rusydi; M. Asnawi (Unity Academy, 2023)
Hikmatul Fadhillah IT School, located in the center of Medan, North Sumatra Province, is the partner choice in this Community Empowerment Program. The Hikmatul Fadhillah IT School, which is based on Integrated Islam, is aimed at Islamic-based human beings whose students are taught to use English and Arabic in their daily lives. During visits to partner locations, the problems faced by partners were the school's knowledge and skills in using information and communication technology (ICT) which resulted in minimal innovation being implemented in schools, especially in financial management. School finances are still conventional or manual based, bookkeeping of income and expenditure transactions still uses books and recording via the Microsoft Excel data processing application, information about school fee payments is still based on information from school groups. The solution offered in this community empowerment program is to provide a web-based information system product for financial management and financial management starting from recording receipts for school fee payments, recording income and expenses accompanied by analysis of reports that can be displayed systemically. After that, training and assistance in managing the school financial services that have been built.